PENGGUNAAN AIR SUPER KRITIS PADA DEPOLIMERISASI NYLON-12 (BATCH PROCESS) - Yusman, Mohamad (Jurnal Rekayasa Lingkungan)
Water at the supercritical state is a new process for the chemical recycling. At this thermodynamic state i.e. Pc = 218 atmospheres and Tc = 374oC , water behaves very differently from its everyday temperament and it is a very good solvent for organic components. Experimental studies show that supercritical water can decompose hydrocarbons/polymers and produce useful products like 2-Azacyclotridecanone /lactam-1 from Nylon-12 (batch process). The decomposition process itself was carried out in batch reaction system in order to get more information about product distributions, time dependence, and scale-up possibilities.Keywords: supercritical water, decomposition, batch, polymer, hydrocarbon